Analisa Kebutuhan Energi Panas untuk Pelunakan Keju Dengan Mesin Pengolah Keju Tipe NT 50 - Susilo, Bambang; Argo, Bambang Dwi; Widiyastuti, Palupi (Jurnal Teknologi Pertanian, 2003)
Cheese is a kind of the product from coagulated milk.  The coagulation processes happen by Rennet enzyme through Lactic Acid Fermentation.  Using of damaged natural cheese mixed with good cheese processes fickle cheese.  The composition of thin product adapted to market need.  The processes consist of sortation, cleaning, cutting, mixing, heating, batch striking and packaging.  The heating stage is the bottleneck of the process, that important to extinguisher microorganism and to melt the cheese rapidly. This research conducted to study the heat input and to study the thermal efficiency of heating cheese with stirrer machine Type NT50.  This parameter is useful to predict the optimal temperature and heating period in relationship with the quality of product.  This study carried out in Laboratory of Husbandry Technology Process, Faculty of Husbandry, Brawijaya University.  The research shows that the thermal input to melt the cheese is 23552.615 kJ.  This energy comprised of accumulation energy in inner cylinder 225.304 kJ and outer cylinder 277.759 kJ.  The water mediums absorb energy 5439.406 kJ and the (raw) material absorbs energy 3439.406 kJ.  The total accumulation heat is 3.793 kJ/kg.  The heat transferred by radiation to surrounding is 139.624 kJ.  The convection heat transfers take place in outer cylinder and the surface of cap.  The accumulation energy in outer cylinder is 642.638 kJ and in the surface 92.635 kJ.  The melting efficiency is 47.885 kJ % and the total efficiency is 47.095 %.  Keyword: cheese, coagulation, energy needs analysis, and heating process